2010
DOI: 10.1111/j.1365-3156.2010.02603.x
|View full text |Cite
|
Sign up to set email alerts
|

‘I never thought that this baby would survive; I thought that it would die any time’: perceptions and care for preterm babies in eastern Uganda

Abstract: Summaryobjective To explore the current care for and perceptions about preterm babies among community members in eastern Uganda.methods A neonatal midwife observed care of preterm babies in one general hospital and 15 health centres using a checklist and a field diary. In-depth interviews were conducted with 11 community health workers (CHWs) and also with 10 mothers, six fathers and three grandmothers of preterm babies. Three focus group discussions were conducted with midwives and women and men in the commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
75
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(79 citation statements)
references
References 29 publications
4
75
0
Order By: Relevance
“…Another study in this region found that most of the mothers interviewed believed that preterm babies could survive if treated properly. However, that study also found that some mothers wished their preterm neonates had never been born [53]. Other studies have also reported stigma, fear, shame, or guilt in association with having a preterm infant [54][55][56].…”
Section: Acceptabilitymentioning
confidence: 88%
See 1 more Smart Citation
“…Another study in this region found that most of the mothers interviewed believed that preterm babies could survive if treated properly. However, that study also found that some mothers wished their preterm neonates had never been born [53]. Other studies have also reported stigma, fear, shame, or guilt in association with having a preterm infant [54][55][56].…”
Section: Acceptabilitymentioning
confidence: 88%
“…In this study, most parents stated that the mother is the KMC provider. In another Ugandan study, most men interviewed felt that women were the sole KMC providers [53]. The majority of parents and providers found use of KMC among neonates who are receiving concurrent medical therapies in the first 48 hours after birth acceptable.…”
Section: Acceptabilitymentioning
confidence: 99%
“…37 A study from Dhaka, Bangladesh, explained that babies are typically bathed soon after birth to purify them from the birth process. 38 Several studies, from Uganda, 39 Ghana 37 and India 40 suggested that in the absence of health facilities prepared to deliver essential newborn care, community members would accept thermoprotective practices such as SSC.…”
Section: Management Of Newborn Hypothermiamentioning
confidence: 99%
“…For example, community health workers, traditional birth attendants and families interviewed in eastern Uganda mentioned many features that correctly identify preterm infants, such as small size at birth, inability to suckle or open the eyes, and skin that appeared wrinkled or similar to a newborn rat. 5 Many families ascribed preterm birth to witchcraft or natural phenomena such as earthquakes. Some expressed fatalism and lack of confidence in the medical system, as conveyed in the words of one mother, "I wished that I had had a miscarriage instead of delivering this preterm, it would be better.…”
mentioning
confidence: 99%
“…I never thought that this baby would survive; I thought that it would die any time." 5 There is an urgent need to understand the context surrounding prematurity in communities, make access to medical services easy and prompt, and increase the capacity to care for small infants both in communities and in facilities.…”
mentioning
confidence: 99%